Improved propagation, early establishment and fruit development of the miracle fruit, (Synsepalum dulcificum Daniell.) - Chen , Xingwei (2013)
Propagation of miracle fruit, Synsepalum dulcificum using cuttings has been investigated for early fruiting planting materials. However, there is very little information on the nutrient requirements during early establishment and growth of the species. Studies on its reproductive biology, fruit set and development are equally important to understand the flowering and fruiting behaviour. The objectives for this study are: (i) to improve the propagation of Synsepalum dulcificum through stem cutting using Indole-3-butyric acid (IBA); (ii) to establish seedlings under different shade levels and nitrogen (N) rates; (iii) to describe the flower and fruit development of Synsepalum dulcificum. Three experiments were conducted to achieve the objectives. In Experiment 1, rooting responses of softwood cuttings of Synsepalum dulcificum as affected by IBA concentrations were conducted. Soft wood stem cuttings were treated with 0 mg/L, 200 mg/L, 400 mg/L, 600 mg/L and 800 mg/L IBA concentrations and arranged in Randomized Complete Block Design (RCBD) with 5 replications. Callus formation started three weeks after sowing and adventitious roots emerged from the basal ends eight weeks after planting. High concentration of IBA (800 mgL-1) increased rooting percentage to 23.64 ± 0.19%. The anatomy of stem cutting at day 0 showed the phloem being surrounded by 2-3 layers of fibers. Root primordial developed from secondary phloems and penetrated the fiber layers 5 weeks after planting. In Experiment 2, growth and physiological responses of miracle fruit seedlings to different shade levels and nitrogen (N) rates were recorded. Six months old seedlings were subjected to 0%, 45% and 75% shade and received 0, 300, 600 and 900 mg N plant-1 year-1. Treatments were arranged in Nested RCBD with 4 replications. Different levels of shades significantly affected plant height, dry weight, leaf area, specific leaf area, number of branches,root:shoot ratio, chlorophyll fluorescence and chlorophyll contents throughout the growing season. Miracle fruits seedlings under 75% shade were taller, had higher photosynthetic rate (1.82 ± 1.113 μ mol m-2 s-1) than other treatments and had high relative growth rate (0.37 g g-1month-1) in the early establishment stage which suggest that this shade level is more suitable for establishment of young miracle fruit plants. Nitrogen fertilization was found to prevent photoinhibition in miracle fruit seedlings in the early establishment stages. Nitrogen rate at 300 mg N plant-1 year-1 was adequate for growth and development since the plant was more efficient in utilizing the available N in low N input (N utilization efficiency = 36.56 mg mg−1). In Experiment 3, flower ontogenesis and fruit development of Synsepalum dulcificum was observed. Flowers and flower buds were processed and observed under light microscope and scanning electron microscope. Miracle fruit flower takes 100 days to develop from reproductive meristem to full anthesis. The flower development can be divided into six stages based on the size and appearance of the flower bud. The fruit with persistence style developed and ripened 90 days after anthesis. Heavy fruit drop was observed at 40 – 60 days after anthesis which contributed to the final fruit set average of 5.06% per plant